Use of Predictive Equations for Energy Prescription Results in Inaccurate Estimation in Trauma Patients. (18th August 2019) - Vasileiou, Georgia; Qian, Sinong; Iyengar, Rahul; Mulder, Michelle B.; Gass, Lindsey M; Parks, Jonathan; Pust, Gerd D.; Rattan, Rishi; Lineen, Edward; Byers, Patricia; Yeh, D. Dante
Abstract: Background: Overfeeding and underfeeding are associated with poor clinical outcomes. In the absence of indirect calorimetry (IC), the Society of Critical Care Medicine/ASPEN recommend prescribing 25–30 kcal/kg. The Harris‐Benedict equation (HBE) multiplied by a stress factor is commonly applied in critically ill patients. We describe the difference between estimated and actual energy needs in critically injured patients. Methods: From March to November 2018, we collected demographics and energy needs determined by continuous IC (started within 4 days) in intubated adults. Ideal or adjusted body weight was used for 25–30 kcal/kg, and HBE was multiplied by a 1.3 stress factor (1.3HBE). Daily requirements up to 14 days, extubation, or death were calculated using all 3 methods and compared with IC. Results: Fifty‐five subjects were included. Median age was 38 [27–58] years, 38 (69%) were male, body mass index was 28 [25–33] kg/m 2, and Acute Physiology and Chronic Health Evaluation II score was 17 [14–24] Mechanism of injury was blunt (38, 69%), penetrating (9, 16%), and burn (8, 15%). By day 14, compared with measured energy requirements by IC, the other methods could result in a cumulative 1827‐kcal (+7%) surplus (1.3HBE), a 1313‐kcal (−5%) deficit (25 kcal/kg), or a 3950‐kcal (+14%) surplus (30 kcal/kg) per patient over a median 9 days. Conclusion: In critically injured patients, predictive equations for energy needs do not account for dynamic metabolic changes over time and could result in underfeeding or overfeeding. Adjusting daily prescription based on continuous IC may result in better individualized treatment.